2014
DOI: 10.1371/journal.pone.0087087
|View full text |Cite
|
Sign up to set email alerts
|

During the Long Way to Mars: Effects of 520 Days of Confinement (Mars500) on the Assessment of Affective Stimuli and Stage Alteration in Mood and Plasma Hormone Levels

Abstract: For future interplanetary manned spaceflight, mental issues, as well as physiological problems, must inevitably be considered and solved. Mars500 is a high-fidelity ground simulation experiment that involved 520 days of confined isolation for six multinational crewmembers. This experiment provided a good opportunity to perform psycho-physiological and psycho-social researches on such missions. To investigate emotional responses and psychological adaptation over long-term confinement, the International Affectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 44 publications
4
45
0
Order By: Relevance
“…It is noticeable that this change occurred simultaneously as several crew members reported feeling less motivated, more depressed and irritable. An increase in depressive symptoms and psychological distress in the second half of the confinement are consistent with findings by other research groups [28,29]. A progressive decrease in positive emotions was also found during the previous 105-days confinement [30] and during Russian space missions [31].…”
Section: Alterations In Personal Valuessupporting
confidence: 90%
See 1 more Smart Citation
“…It is noticeable that this change occurred simultaneously as several crew members reported feeling less motivated, more depressed and irritable. An increase in depressive symptoms and psychological distress in the second half of the confinement are consistent with findings by other research groups [28,29]. A progressive decrease in positive emotions was also found during the previous 105-days confinement [30] and during Russian space missions [31].…”
Section: Alterations In Personal Valuessupporting
confidence: 90%
“…Firstly, crew members reported being cautious with expressing negative feelings towards each other due to the risk of harming their relationships. Instead interpersonal tension seemed to be expressed by social withdrawal, an observation also made by other researchers [29] and which is consistent with results from previous confinement studies [17]. Such more subtle expression of tension may explain why other researchers involved in the confinement study concluded that cohesion did not deteriorate over time [34].…”
Section: Values As Sources Of Crew Tensionsupporting
confidence: 89%
“…We ask, is it too big a dream to cure anthropocene syndrome, first? We ask, rather than worrying about the mental health and neurotransmitter levels of those traveling to Mars [150], or the ways in which an unplanned pregnancy during an interplanetary mission "could put the entire crew in danger" [151], could we use this valuable time here on Earth to research the kind of life we would want on Mars? What is the endgame here?…”
Section: Discussionmentioning
confidence: 99%
“…Thus may be a flexibility of the subjects. Particularly, Wang Y, et al [20], had conducted a questionnaire-based investigation of emotional responses and psychological adaptation over 520 days' isolation, and results had demonstrated an obvious bias on valence rating for unpleasant stimuli with time (p<0.05), thus may explain the elevation of serotonin at period two. Furthermore, the presence of increased psychosocial issues caused by long-term isolation had been proved by many researches [21][22][23][24][25][26].…”
Section: Metabolic Responses To 520 Days' Isolationmentioning
confidence: 99%